PESAN-PESAN DAKWAH DALAM FILM JANGAN BUAT AKU BERDOSA (STUDI ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE) - Azizah, Adelia Nur; Fajar, M. Samson; Nur, Muhammad (DECODING: Jurnal Mahasiswa KPI, 2021)
The message of da'wah is what is conveyed in the process of delivering da'wah. In communication, da'wah messages are also called messages, namely symbols. Film as a propaganda medium means a tool used in da'wah activities or an intermediary in delivering da'wah messages. Film is a powerful medium of communication, not only for entertainment, but also for education and information. In fact, Jakob Sumardjo, from the center for film and television education, stated that films act as experiences and values. It is very possible as a means of transmitting stimuli in society as well as to be used as a means of conveying Islamic symbols to the wider community. Because the film as a communication device, is able to absorb the communicant widely. An example of a film as a propaganda medium is the film Jangan Buat Aku Berdosa (Don't Make Me Sin), which is a short film made by the Jurnalis Pejuang of Pena Production (JP3) and directed by Gusti Adi Pranoto. 39 Minutes in duration, consisting of 3 episodes released on January 12, 2018 from screenwriter Fia Handari. The film Jangan Buat Aku Berdosa consists of 3 episodes. Each episode is titled Jangan Buat Aku Berdosa, Memantaskan Diri and Jika Karna-Nya. This film has also won an award as "Best Lampung Film" at the 2017 Lampung Islamic Film Festival. Nadin and Fikri are the main characters in this film. This type of research was descriptive qualitative research. Qualitative descriptive research is a research that seeks to describe a phenomenon or event systematically according to what it is. Qualitative descriptive research is research conducted to examine groups of people, conditions, thoughts or an event in the present which aims to describe what it is about a variable, symptom, or situation. The results of the study showed that there were messages of da'wah in the film, Jangan Buat Aku Berdosa, including; Prohibition of adultery, covering aurat (intimate part), and marriage. That the act of courtship as shown in the scene is an act of approaching adultery. An act that is prohibited in Islam. It can be concluded that, there were messages of da’wah and the study of semiotics of Ferdinand De Saussure in the film Jangan Buat Aku Berdosa.